PERWUJUDAN SPECIAL EFFECTS MAKEUP KARAKTER LEMBU SURO DALAM VISUAISASI MITOLOGI JAWA MENGGUNAKAN LIQUID LATEX - Putri Ardiana; Maspiyah, Maspiyah; Kusstianti, Nia; Megasari, Dindy Sinta (Program Studi Pendidikan Tata Rias, 2025)
Lembu Suro is a character from Javanese mythology depicted as a half-human, half-bull figure with angry, powerful, and mystical characteristics. Visualizing this character requires an artistic approach that is not only strong in aesthetics but also capable of expressing cultural narratives emotionally. The technique used in this study is prosthetic-based Special Effects Makeup (SFX Makeup). This research aims to: (1) produce a Special Effects Makeup design for Lembu Suro that reflects the physical and emotional characteristics of the Javanese mythological figure, particularly the expression of anger; (2) determine the realization of the Lembu Suro character using liquid latex; and (3) assess respondents’ evaluations of the character's visualization. The method employed is Research and Development (R&D) using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The design was validated by three experts (Makeup artistry, fine arts, and SFX Makeup), while the realization was assessed by 30 trained respondents in character Makeup. The results showed that the first design was selected with a feasibility percentage of 96%, indicating its ability to reflect the physical and emotional traits of the mythological character, especially the expression of anger. The realization process involved lifecasting, sculpting, molding, prosthetic application, painting, and finishing. Respondents' evaluation of the character realization received an average percentage score of 88,67%, categorized as “Highly Appropriate,” indicating that the character realization aligned very well with the designed concept. This study demonstrates that the use of liquid latex in SFX Makeup techniques is effective in visualizing mythological characters emotionally and narratively, and it can serve as a medium for preserving local culture through a modern artistic approach based on character Makeup. Keywords: Special Effects Makeup, Lembu Suro, liquid latex, Javanese mythology, character Makeup